Synthesis, Characterization, and In Vitro Studies of an Reactive Oxygen Species (ROS)-Responsive Methoxy Polyethylene Glycol-Thioketal-Melphalan Prodrug for Glioblastoma Treatment - Natalia Oddone; Frank Boury; Emmanuel Garcion; Andreas M. Grabrucker; Andreas M. Grabrucker; Andreas M. Grabrucker; M. Carmen Martinez; Federica Da Ros; Anna Janaszewska; Flavio Forni; Maria Angela Vandelli; Giovanni Tosi; et al. (Frontiers Media S.A., 2020)
Glioblastoma (GBM) is the most frequent and aggressive primary tumor of the brain and averages a life expectancy in diagnosed patients of only 15 months. Hence, more effective therapies against this malignancy are urgently needed. Several diseases, including cancer, are featured by high levels of reactive oxygen species (ROS), which are possible GBM hallmarks to target or benefit from. Therefore, the covalent linkage of drugs to ROS-responsive molecules can be exploited aiming for a selective drug release within relevant pathological environments. In this work, we designed a new ROS-responsive prodrug by using Melphalan (MPH) covalently coupled with methoxy polyethylene glycol (mPEG) through a ROS-cleavable group thioketal (TK), demonstrating the capacity to self-assembly into nanosized micelles. Full chemical-physical characterization was conducted on the polymeric-prodrug and proper controls, along with in vitro cytotoxicity assayed on different GBM cell lines and "healthy" astrocyte cells confirming the absence of any cytotoxicity of the prodrug on healthy cells (i.e. astrocytes). These results were compared with the non-ROS responsive counterpart, underlining the anti-tumoral activity of ROS-responsive compared to the non-ROS-responsive prodrug on GBM cells expressing high levels of ROS. On the other hand, the combination treatment with this ROS-responsive prodrug and X-ray irradiation on human GBM cells resulted in an increase of the antitumoral effect, and this might be connected to radiotherapy. Hence, these results represent a starting point for a rationale design of innovative and tailored ROS-responsive prodrugs to be used in GBM therapy and in combination with radiotherapy.